2019
DOI: 10.35307/saltel.v2i2.35
|View full text |Cite
|
Sign up to set email alerts
|

Shadowing Technique; Teaching Listening Skill to ESOL Learners in University

Abstract: The purpose of this paper is to report the effect of Shadowing Technique on students’ listening skills achievement. Therefore, the experimental research was applied and the technique on collecting the data was administrating pre- and post- tests to the experiment and control groups, which consisted of 40 students in each group. Then, t-test was employed on analyzing the data. As a result, there was a significant difference between the mean of experimental and control groups (F = 8.92, p=. 003 < .05). Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…The finding of this study suggested that the listening comprehension skill of the experimental group could have improved due to the use of the shadowing technique in class in comparison with the control group. Similar results have been shown in previous studies in different contexts, especially in Asia (Dwi, 2019;Ginting, 2018;Hamada, 2011;Saito et al, 2011;Shimomura, 2018;Sumiyoshi and Svetanant, 2017;Zuhriyah, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…The finding of this study suggested that the listening comprehension skill of the experimental group could have improved due to the use of the shadowing technique in class in comparison with the control group. Similar results have been shown in previous studies in different contexts, especially in Asia (Dwi, 2019;Ginting, 2018;Hamada, 2011;Saito et al, 2011;Shimomura, 2018;Sumiyoshi and Svetanant, 2017;Zuhriyah, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…One of them is technique shadowing. Techniques Shadowing have been widely used in foreign language learning, such as English by (Ginting 2019), Japanese by (Basri et al 2020) and other foreign languages. In learning foreign languages, Techniques shadowing can be applied in 4 language skills listening, reading, writing, and speaking.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the significant importance of connected speech for listening skills as well as some general challenges regarding teaching and learning pronunciation, there is a need for research on the effective technique to help learners out with improving their pronunciation. In this respect, shadowing has proved to positively affect learners' oralaural skills such as general listening comprehension (Tamai, 1997;Onaha, 2004;Lin, 2009;Chung, 2010;Kato, 2009;Ginting, 2019), bottom-up processing and recognizing words (Hamada, 2016a), different aspects of pronunciation namely unfamiliar accents, intonation, production fluency (Astuti, 2020;Hamada & Suzuki, 2021), rhythm (Okada, 2002;Omar & Umehara, 2010), prosody (Kusumoto, 2015), which accounts for up to 40 % in communication meaning. However, no research has focused on the effects of shadowing on consonant-vowel linking although acquiring this skill is an essential part of foreign language learning and teaching.…”
Section: Introductionmentioning
confidence: 99%